In Vitro Alpha-Amylase Inhibitory Activity of Microencapsulated Cosmos caudatus Kunth Extracts - Anna Safitri; Anna Roosdiana; Ellysia Hitdatania; Savira Ayu Damayanti (Indonesian Journal of Chemistry, 2022)
The existence of phytochemicals in Cosmos caudatus Kunth, predominantly phenolic compounds, offers several health benefits. Nevertheless, the bioactive compounds are usually susceptible to degradation, and therefore may reduce their biological activity. This work aims to carry out microencapsulation of C. caudatus K. extracts by spray drying technique. The in vitro alpha-amylase inhibitory activity of the microencapsulated product is also investigated. The effect of manufacturing conditions, including pH, the concentration of wall materials, and stirring time, was evaluated. The optimal conditions for microcapsules formation were selected based on the activity of microcapsules as inhibitors for the alpha-amylase enzyme, pointing out by the lowest number of IC50. Results showed that microcapsules prepared in pH 4, 0.05% of chitosan, and 90 min stirring time had optimum efficiency, with the IC50 value of 92.85 ± 1.21 μg/mL. The FTIR (Fourier-Transform infrared) analysis showed that the –C–N stretching amine functional group appeared at wavenumber 1285 cm–1, and the –P=O phosphate bending appeared at 1206 cm–1. Characterization with PSA (particle size analyzer) and SEM (scanning electron microscope) indicated that microcapsules had predominantly spherical forms with a mean diameter of 38.92 μm. This work confirms the important role of microencapsulation in developing plant extracts with retained biological functionalities.